Correlations Amongst Functional and Morphological Attributes and Oxidative Markers of Fresh and Cryopreserved Semen of Gir and Murrah Bulls - Patel, Tapasvi M; Dhami, AJ; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was undertaken during the winter season on healthy mature Gir cattle and Murrah buffalo bulls (n=3 each). The semen samples (6 ejaculates/bull, total 36 ejaculates) collected in the morning using artificial vagina were evaluated for routine seminal attributes, including acrosomal and plasma membrane integrity. The samples were then diluted @ 100 million sperm/ml with tris fructose yolk glycerol extender without and with sericin @ 0.1, 0.25, 0.5 and 1.0% (w/v), filled in French mini-straws, and frozen in LN2 using biofreezer as per standard freezing protocol. Straws were thawed in water bath at 37°C for 30 sec and evaluated for post-thaw quality, viz., motility, viability, morphology, acrosome integrity and plasma membrane integrity (HOST). Lipid peroxidation (malondialdehyde - MDA production) and activities of enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) were assessed as oxidative markers in seminal plasma of freshly diluted and frozen-thawed semen samples. Sericn at 0.5% level significantly (p<0.01) improved the post-thaw sperm quality with reduced oxidative stress in both the species. The breed-wise correlation coefficients (r) among sperm quality attributes and oxidative markers were studied in fresh and frozen-thawed semen of each species, and also for fresh with frozenthawed semen. The findings revealed significant interrelationships amongst most of the attributes of fresh as well as post-thawed semen and also of fresh semen attributes with those of cryopreserved semen including oxidative markers in both the species. Sperm motility estimation in fresh, pre-freeze and post-thawed semen was a legitimately good indicator of quality of spermatozoa at various steps of semen processing/freezing, and its fertilizing potential. Thus, the sperm motility, HOS test and either MDA or SOD/GPx activity alone may be used as valuable and practical tools for routine assessment of bovine semen quality considering significant correlations found between them.